Pelayanan Publik Berbasis Digital di Kantor Desa Santur Kecamatan Barangin Kota Sawahlunto - Nazirwan, Nazirwan; Anita, Devi; Kurniawan, Novian Anggi (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
The objective of this study is to assess the digital public services provided at the Santur Village Office, located in the Barangin District of Sawahlunto City. The implementation of electronic-based governance aims to enhance the efficiency, effectiveness, and interactivity of public services. e-Government essentially refers to the utilization of information technology to enhance communication and interaction between the government and other stakeholders such as residents, entrepreneurs, and other agencies. The provision of Digital-Based Public Services is inherently dependent on the internet network, and the presence of poor internet connections poses a significant hindrance to the smooth execution of these services. The employed research methodology is a descriptive qualitative approach. The group of informants comprised 23 individuals, including the Village Head, Village Secretary, Head of Services, Village Administration Officer, Hamlet Head, and Community members. The data source utilized is original data acquired firsthand from informants. Secondary data is derived from the data collected at the Santur Village Office, located in the Barangin District of Sawahlunto City. The research findings indicate that the Digital-Based Public Services provided by the Santur Village Office in the Barangin District of Sawahlunto City are suboptimal. This is primarily due to the disparity in the IT skills of the Village Apparatus personnel, as well as their limited proficiency in the IT sector. The implementation of online learning is influenced by factors such as the availability of internet connections, restricted ownership of internet-accessible mobile phones among village communities, and the stability of internet signals.